Review of The Super Resolution Microsphere Optical Imaging Technique - Hrata, Zainab Abdali; Rajab, Fatema H.; Stanescu, Sorin L. (Al-Nahrain Journal for Engineering Sciences, 2024)
In this work we performed a review regarding the improvement of microscopical optical imaging assisted by using microspheres, focusing on the most recent technologies. We have been reviewed the utilizing of the superlens and nanojet concepts in order to understand the working principles of microspheres in terms of magnification and resolution improvement. Some researches about the parameters effecting on microsphere imaging technique have been presented including the effect of microsphere’s material and size, the effect of immersion medium, and the plasmonic layer effect. Additionally, some applications that serve from this technique have been illustrated.